Development of a participatory approach for mapping climate risks and adaptive interventions (CS-MAP) in Vietnam’s Mekong River Delta - Bui Tan Yen; Nguyen Hong Son; Le Thanh Tung; Amjath-Babu, Tharayil Shereef; Leocadio, Sebastian (Elsevier, 2019)
The El Niño-Southern Oscillation (ENSO) in 2016 adversely affected Vietnam particularly in the Mekong River Delta (MRD), where more than 90% of the country’s rice export is produced annually. During that time, salinity intrusion and drought significantly affected agricultural production in the area. Furthermore, flooding is another recurring event in the area that is increasing in frequency. An assessment conducted by CGIAR Centers showed that even as warnings were provided by the government for the 2016 ENSO, these were not translated into appropriate preparations and responsive actions for agriculture. To address this critical issue, the Department of Crop Production (DCP) of the Ministry of Agriculture and Rural Development (MARD) of Vietnam, and CGIAR Research Program on Climate Change, Agriculture and Food Security in Southeast Asia (CCAFS- SEA) collaborated to develop and test an participatory approach for mapping climate risks and adaptive interventions (CS-MAP) to recognize climate-related risks, identify potentially affected areas and develop regional and provincial adaptation plans for rice production. The CS-MAP is a participatory approach involving experts from various local and national offices for: (1) identifying climate-related risks; (2) delineating affected areas and risk levels; (3) proposing corresponding adaptive plans; (4) fine tuning and verifying proposed measures; and (5) developing integrated provincial and regional adaptation plans. Risks and adaptive interventions maps were developed for normal and ENSO years by using technical data (i.e. topography and hydrology), infrastructures (i.e. dikes, road and canals), and local observations. CS-MAP is now is under various stages of development and implementation in 13 MRD provinces highlighting the organizational uptake and integration of the approach.